STABILITY ANALYSIS OF ORTHOTROPIC RECTANGULAR PLATES COMPRESSED ALL OVER THE CONTOUR - Korobko, Andrey Victorovich; Savin, Sergey Yurievich; Ivlev, Ivan Andreevich (Journal of Applied Engineering Science, 2017)
The article describes the stability analysis of elastic orthotropic rectangular plates with combined boundary conditions (combination of simple supporting and clamping along the sides). The external load compresses a plate along all over the contour. Authors propose to apply the form factor interpolation method (FFIM) to calculate the critical load of buckling. The FFIM is based on the functional relationship between integral geometric parameter of the midplane such as the form factor and the critical force of the buckling. It was obtained the approximate analytical expressions for the critical force of orthotropic rectangular plates. The form factor and the flexural stiffness ratios are parameters of these approximate expressions. The calculation results are compared with the FEM solutions obtained in the program SCAD Office and demonstrate good accuracy. The proposed approach can be extended to other forms of plates, boundary condition combinations, as well as the types of loading.
Keywords: Orthotropic plates; Combined boundary conditions; The form factor interpolation method; The FEM; Stability analysis; Loads; Compression